Ocorrência de Dictyla monotropidia Stål (Hemiptera: Tingidae) em Cordia verbenacea Al. DC no Brasil - Rosa, Daniel D. [UNESP]; Basseto, Marco A. [UNESP]; Feliciano, Fernanda; Neves, Monica B.; Baldin, Edson Luiz Lopes [UNESP] (Entomological Soc Brasil, 2008)
Recently, Dictyla monotropidia Stal was observed feeding on plants of black sage (Cordia verbenacea Al. DC). The colonies of this insect were observed on abaxial surface of leaves, with nymphs and adults sucking the phloem sieve, causing spot, yellow aspect and leaf fall. D. monotropidia was already related as pest in other Cordia species in countries of Central and South America. Although, this is the first report of this insect attacking plants of C. verbenacea in Brazil.
Occurrence of Dictyla monotropidia Stal (Hemiptera : Tingidae) on Cordia verbenacea Al. DC in Brazil
Keywords: lace bug; medicinal plant; black sage